Alopecia and Iron Deficiency: An Interventional Pilot Study in Primary Care to Improve the Request of Ferritin - Maria Salinas; Maria Leiva-Salinas; Emilio Flores; Maite López-Garrigós; Carlos Leiva-Salinas (Advances in Hematology)
Background. The aim was to study the demographic and laboratory pattern of primary care patients with alopecia undergoing laboratory testing, more specifically, the request of hemoglobin and ferritin and values showing anemia and iron deficiency, and to evaluate the effects of an intervention involving automatic ferritin registration and measurement when not requested. Methods. Retrospective and prospective observational cross-sectional studies were conducted, as well as an intervention to automatically register and measure ferritin when not requested by the general practitioner. Results. There were 343 and 1032 primary care laboratory requests prompted by alopecia in the retrospective and prospective studies. Hemoglobin was requested in almost every patient and ferritin in 88%. 5% of the cohort had anemia, and 25% had iron deficiency. The intervention registered and measured that 123 ferritin and 24 iron deficiencies were detected in patients with alopecia, all women, at a cost of 10.6€. Conclusion. Primary care patients with alopecia and laboratory tests request were mainly young female. Our intervention added ferritin when not requested, detecting iron deficiency in 27.9% of women, potentially avoiding the adverse effects of iron deficiency on hair loss.